2011
DOI: 10.1055/s-0031-1297986
|View full text |Cite
|
Sign up to set email alerts
|

Decompression Procedure using a Microendoscopic Technique for Thoracic Myelopathy Caused by Ossification of the Ligamentum Flavum

Abstract: The authors found that the microendoscopic technique could be applied to decompression surgery for thoracic OLF. The procedure could provide a sufficient decompression with minimum damage to the paraspinal muscles. However, the microendoscopic procedure should be indicated only for select thoracic OLF, such as OLF without fusion at the middle of the spinal canal and OLF without dural ossification, because of its technical difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…Some research showed that, if OLF encroached dura mater, we can select 'floating method' which is a microscopic technique for decompression to avoid CSF leakage. 73,74 Another serious surgical complication in thoracic OLF surgery is spinal cord injury. 62,75,76 Several procedures were followed with the aim of minimizing the risk of spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Some research showed that, if OLF encroached dura mater, we can select 'floating method' which is a microscopic technique for decompression to avoid CSF leakage. 73,74 Another serious surgical complication in thoracic OLF surgery is spinal cord injury. 62,75,76 Several procedures were followed with the aim of minimizing the risk of spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few case reports are available on the use of this approach for treatment of thoracic OLF. Ikuta et al reported successful microendoscopic decompression of OLF at T11/12, but concluded that because of technical difficulties, this procedure is only indicated for particular cases of thoracic OLF, such as those without fusion at the middle of the spinal canal and OLF in the absence of dural ossification [25]. Wang et al also reported successful treatment of OLF at T10/11 using MISS and an expandable tubular retractor system to enable extensive retraction of the surgical area (a 3-cm skin incision is required) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Pro ble mem jest znacz nie ogra ni czo na kwali fi ka cja do te go ty pu za bie gów. Zrost skost nień z oponą twar dą rdze nia krę go we go spra wia, że za bieg ope racyj ny sta je się trud ny i znacz nie wzra sta ry zy ko śródo pe ra cyj ne go uszko dze nia opo ny twar dej z wy cie kiem pły nu mó zgo wo -rdze nio we go oraz za pa le nia opon mózgo wo -rdze nio wych [39]. Le cze nie ope ra cyj ne nie zawsze przy no si po zy tyw ny re zul tat.…”
Section: Treatmentunclassified
“…The seriously limited qualification criteria for this type of surgery constitute a major problem, however. The adhesion of ossifications to the dura mater of the spinal cord complicates surgery and significantly increases the risk of intraoperative damage to the dura mater with seepage of cerebro-spinal fluid and meningitis of the brain and spinal cord [39]. Surgical treatment does not always produce a positive outcome.…”
Section: Podsumowaniementioning
confidence: 99%